Design and implementation of IoT-based motorcycle keyless ignition and starter using RFID and Blynk - Budiada, I Made; Ida Bagus Irawan Purnama; Putri Alit Widyastuti Santiary; I Ketut Swardika; I Nyoman Kusuma Wardana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Motorcycles are one of the most widely used means of transportation in the community. However, this widespread usage has led to an increase in thefts, especially when motorcycles are not equipped with adequate security systems. Statistical data shows that motorcycles have the highest theft rate compared to other vehicles. To address this issue, an enhanced security system is necessary. This study proposes the use of Radio Frequency Identification (RFID) sensor and the Blynk application to provide additional security for motorcycles. The RFID system will only be accessible using the motorcycle owner's e-KTP (electronic Indonesian Identity Card) or other registered cards to start the vehicle. Additionally, the Blynk mobile application allows for vehicle control (ON and OFF) via Wi-Fi and provides real-time monitoring of the vehicle's status. This application enables motorcycle activation remotely via Wi-Fi, with a range of approximately 10 meters. Meanwhile, there is a 4-second delay to start the motor starter using e-KTP. Test results indicate that this IoT-based keyless ignition and starter system is effective in enhancing motorcycle security. With this system, motorcycles have a dual-layer security mechanism to minimize theft attempts.